A preparation method and application of polytetrafluoroethylene ceramic composite membrane

Through solvent-based emulsion coating method and continuous hot calendering treatment, combined with optimized inorganic filler ratio, the uneven performance and surface defects of polytetrafluoroethylene ceramic composite film in 5G or millimeter wave applications are solved, and the combination of high thermal conductivity and low dielectric loss is achieved, and it is suitable for the preparation of high-frequency copper clad materials.

CN118812898BActive Publication Date: 2025-03-14NINGBO TURBULENCE ELECTRONIC MATERIALS CO LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411297917.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-09-18
Publication Date
2025-03-14
Estimated Expiration
2044-09-18

AI Technical Summary

Technical Problem

The existing polytetrafluoroethylene ceramic composite film materials have uneven performance, unstable and surface defects in 5G or millimeter wave communication applications, and it is difficult to achieve both high thermal conductivity and low dielectric loss.

Method used

A high-density and uniform thickness polytetrafluoroethylene ceramic composite film was prepared by solvent-based emulsion coating method, combined with step-by-step volatile solvents and continuous hot-calendering treatment, and the thermal conductivity of the material was improved by optimizing the types and proportions of inorganic fillers.

Benefits of technology

The continuous roll-in production of polytetrafluoroethylene ceramic composite film is realized, eliminating micropores and hollow defects on the film surface, improving the density and tensile strength of the material, with high thermal conductivity and low dielectric loss characteristics, and is suitable for high-frequency applications.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118812898B_ABST
    Figure CN118812898B_ABST
Patent Text Reader

Abstract

The present invention discloses a preparation method and application of a polytetrafluoroethylene ceramic composite film, and relates to the field of communication material manufacturing. The present invention adopts a coating process, a step-by-step volatilization of a solvent, and a step-by-step continuous hot calendering, that is, a coating method is used to prepare a polytetrafluoroethylene ceramic raw film, so that the raw film is subjected to a step-by-step "heat treatment-hot calendering" treatment, thereby realizing the continuous roll production of the polytetrafluoroethylene ceramic film; in addition, the present invention adopts a continuous hot calendering method to gradually increase the material density and eliminate film-forming defects, and the prepared composite film has uniform density and thickness, and the tensile fracture strength is better than the composite film produced by the existing aqueous emulsion coating process; and the method described in the present invention can obtain a polytetrafluoroethylene ceramic composite film with high thermal conductivity and high filler content, as well as a high-frequency copper-clad laminate material with high thermal conductivity; and it has high thermal conductivity and low dielectric loss characteristics at high frequencies, and is suitable for high-power, high-frequency, and high-speed printed circuit board products with high requirements for thermal management.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of communication material manufacturing, and particularly relates to a preparation method of a polytetrafluoroethylene ceramic composite film and application thereof. Background Art

[0002] At present, in the practical applications of 4G, 5G and even millimeter wave communications, especially in the field of high-frequency printed circuit board substrates (high-frequency PCB substrates) for 5G or millimeter wave communications, there are increasingly higher requirements for the dielectric constant and dielectric loss of the material itself, as well as the thermal conductivity of the material. Among them, PTFE material plays an irreplaceable role in the above applications with its unique dielectric constant stability and extremely low dielectric loss performance among all polymer materials, and is one of several core materials. Expanded polytetrafluoroethylene film is generally made by a biaxial stretching process. Because it contains voids, it cannot be used as a substrate material for 5G or millimeter wave communications; while polytetrafluoroethylene ceramic composite membrane materials prepared by non-expanded process are increasingly attracting widespread attention from researchers at home and abroad in this field, and have a huge industrial application market and prospects.

[0003] At present, there are mainly the following routes for the preparation of polytetrafluoroethylene ceramic composite membrane materials:

[0004] (1) Glass fiber dipping method

[0005] The PTFE-glass fiber cloth prepared by the PTFE-woven glass fiber cloth dip coating process has a simple process and low technical difficulty, but the mesh effect brought by the woven glass fiber cloth contained therein limits the application of the material in the millimeter wave field, and it is a non-isotropic material;

[0006] (2) Die turning method

[0007] The process of "mixing-molding-sintering-turning" was adopted to prepare a polytetrafluoroethylene ceramic composite membrane material without glass fiber cloth reinforcement; the turning process can be produced continuously, with low cost, and the membrane thickness is 15-50μm, which can be adjusted; however, the turning process limits the ceramic content in the material, and the ceramic content is generally not more than 10wt%, and the turning membrane with higher filler content has many surface defects;

[0008] (3) Extrusion calendering method

[0009] US4335180A discloses that microfibers, inorganic fillers and flocculants are mixed into PTFE emulsion in sequence, and then filtered and dried to obtain a fluorine-containing resin mixture, which is pressed into a plate and then laminated with copper foil to obtain a fluorine-containing resin-based copper-clad laminate without glass fiber cloth reinforcement. This method has a large sheet thickness and cannot achieve continuous production of polytetrafluoroethylene membranes. In addition, a large amount of fluorine-containing compound wastewater is generated during the production process.

[0010] Chinese patent CN2013100250727 introduces a method for preparing a PTFE copper-clad laminate with a high filler content: first, fluororesin powder is mixed with an inorganic filler, then an organic lubricant is added, and the mixture is stirred into a dough-like object, and then extrusion, calendering and other processes are performed to obtain a sheet, the sheet is heat-treated (250°C / 6h), and then the sheet is impregnated with a fluororesin dispersion, and then dried, baked and sintered to obtain a sheet with few pores and a layer of resin film on the surface; this method also cannot achieve continuous production of polytetrafluoroethylene membranes;

[0011] (4) Water-based emulsion coating-sintering process

[0012] Chinese patent CN104175686A discloses that a fluororesin emulsion, an inorganic filler and a thickener are mixed to obtain a dispersion, and then the dispersion is coated on a releasable substrate and baked, and then the resin layer is separated from the substrate, and then a composite dielectric substrate is prepared by cutting, laminating and sintering.

[0013] The relevant research group of Tianjin No. 46 Institute prepared PTFE water-based emulsion, ceramic powder filler, surfactant, silane coupling agent, thickener and other raw materials into slurry, and realized the production process of polytetrafluoroethylene ceramic membrane on polyimide base film-mirror stainless steel belt by coating-sintering method;

[0014] However, according to the process disclosed in the above route, the film produced has many microscopic defects (cracks, pores, etc.), and the density of the material needs to be improved; in addition, the content of ceramic fillers added by thickeners in this route is still limited; and too high an addition amount will cause the above process to be unable to obtain a continuously stable slurry.

[0015] It can be seen that polytetrafluoroethylene itself is a thermoplastic resin material, but the melt viscosity of PTFE itself is extremely high, and it almost does not flow above the melting temperature, making it difficult to process and shape using ordinary thermoplastic resin methods. Therefore, considering the shortcomings of existing routes and the characteristics of PTFE materials themselves, the development of a new molding process for polytetrafluoroethylene ceramic composite membranes has great technical and application significance. Summary of the invention

[0016] The main objectives of the present invention are: on the one hand, to provide a method for preparing a polytetrafluoroethylene ceramic composite membrane that can be mass-produced and has stable quality, so as to reduce the problems of uneven thickness and performance, instability, and surface defects in the production process of the existing aqueous emulsion coating-sintering process; on the other hand, to provide a method for preparing a high thermal conductivity polytetrafluoroethylene ceramic composite membrane and its application, which are used to prepare a high thermal conductivity polytetrafluoroethylene ceramic-based high-frequency copper clad laminate with a thermal conductivity of not less than 1.2W / (m•K).

[0017] As a first aspect of the present invention, in order to achieve the above-mentioned purpose, the present invention provides a method for preparing a polytetrafluoroethylene ceramic composite membrane, comprising the following steps:

[0018] Step 1, fully mixing fluororesin powder, inorganic filler powder, rheological additive and aromatic hydrocarbon mixed solvent to obtain a solvent-based emulsion;

[0019] Step 2, coating the solvent-based emulsion in step 1 on the base film, and performing a first baking treatment at 70-150° C. to prepare a polytetrafluoroethylene ceramic raw film coil coated on the film;

[0020] Step 3, performing the first continuous hot calendering treatment, the hot pressing temperature is 80-140°C;

[0021] Step 4, baking for the second time at 200-280°C;

[0022] Step 5, performing a second continuous hot calendering treatment at a hot pressing temperature of 80-140° C. to obtain a polytetrafluoroethylene ceramic membrane coil of a composite base membrane;

[0023] Step 6: sintering at a high temperature of 330-380° C. and obtaining a polytetrafluoroethylene ceramic composite membrane after cooling.

[0024] Specifically, the production process of the above-mentioned polytetrafluoroethylene ceramic composite membrane includes the following steps:

[0025] Step 1, fully mixing fluororesin powder, inorganic filler powder, rheological additive, and high / low boiling point aromatic hydrocarbon solvent to obtain a uniformly dispersed solvent-based emulsion;

[0026] Step 2: using a horizontal coating device, quantitatively and evenly coating the emulsion in step 1 on the membrane; after a segmented temperature baking treatment, the temperature setting range of each segment is 70-150° C., and the total residence time is 3-10 min (the residence time of each temperature segment is the same), the low boiling point aromatic hydrocarbon solvent in the system is volatilized, and a polytetrafluoroethylene ceramic raw membrane coil coated on the membrane is prepared;

[0027] Step 3, subjecting the raw membrane prepared in step 2 to a first continuous hot calendering treatment, with a hot pressing temperature of 80-140° C., a hot calendering line speed of 0.2-3 m / min, and a calendering roller top pressure of 5-60 t, to eliminate micropores in the membrane material, and obtain a composite base membrane containing a polytetrafluoroethylene ceramic membrane coil containing a high-boiling point aromatic hydrocarbon solvent;

[0028] Step 4, passing the coil prepared in step 3 through a tunnel ventilation oven, wherein the oven temperature is set in sections, each section temperature setting range is 200-280°C, and the total residence time is 2-10min (the residence time in each temperature section is the same), to volatilize the high boiling point aromatic hydrocarbon solvent therein;

[0029] Step 5, subjecting the coiled material treated in step 4 to a second continuous hot calendering treatment on a continuous hot calendering machine, with a hot pressing temperature of 80-140° C., a hot calendering line speed of 0.2-3 m / min, and a calendering roller top pressure of 5-60 t, to obtain a polytetrafluoroethylene ceramic membrane coiled material of a composite base membrane;

[0030] Step 6: sinter the coiled material treated in step 5 in a high temperature oven at a sintering temperature of 330-380° C. for 1-8 hours. After cooling, a polytetrafluoroethylene ceramic composite membrane is obtained.

[0031] Preferably, the fluororesin powder comprises a first component and a second component; the first component is selected from at least one of polytetrafluoroethylene (PTFE) or modified polytetrafluoroethylene; the second component is selected from any one or both of tetrafluoroethylene-perfluoroalkyl vinyl ether copolymer (PFA) or polyperfluoroethylene propylene (FEP).

[0032] Preferably, the weight of the first component is not less than 85 parts based on 100 parts by weight of the entire fluororesin powder.

[0033] Preferably, the fluororesin powder is a suspended fine powder with a particle size of 20-40 μm.

[0034] Preferably, the inorganic filler powder is a mixture of one or more of silicon dioxide, glass powder, hollow glass beads, titanium dioxide, barium titanate, barium strontium titanate, aluminum oxide, aluminum nitride, boron nitride, calcium carbonate, aluminum hydroxide, magnesium hydroxide, mica, glass fiber, quartz fiber, and zinc oxide.

[0035] Preferably, the amount of the inorganic filler powder used accounts for 5 vol% to 75 vol% of the total volume of the fluororesin and the filler.

[0036] Preferably, the rheological additive is a solvent-based rheological additive, which is used to improve the anti-settling performance of the emulsion.

[0037] Preferably, the rheological additive is used in an amount of 0.05-0.5 wt % of the weight of the fluororesin.

[0038] Preferably, the aromatic hydrocarbon mixed solvent comprises a mixed solvent or lubricating aid composed of one or more aromatic hydrocarbon solvents with a distillation range of 100-200°C and one or more aromatic hydrocarbon solvents with a distillation range of 230-350°C.

[0039] Preferably, based on 100 parts by weight of the total fluororesin, the amount of the one or more aromatic hydrocarbon solvents with a distillation range of 100-200° C. added is 20-70 parts by weight; the amount of the one or more aromatic hydrocarbon solvents with a distillation range of 230-350° C. added is 5-15 parts by weight.

[0040] Preferably, the one or more aromatic hydrocarbon solvents with a distillation range of 100-200° C. are, for example, mixed xylene (distillation range 137-143° C.) and an aromatic hydrocarbon solvent with a distillation range of 161-179° C., or a mixture of two of these.

[0041] Preferably, the one or more aromatic hydrocarbon solvents with a distillation range of 230-350°C are, for example, one or a mixture of two of an aromatic hydrocarbon solvent with a distillation range of 246-304°C, an aromatic hydrocarbon solvent with a distillation range of 215-295°C, and an aromatic hydrocarbon solvent with a distillation range of 300-350°C.

[0042] Preferably, the base film is any one of polyimide film, aluminum foil, copper foil and stainless steel foil.

[0043] Preferably, the aromatic hydrocarbon solvent volatilized in step 2 and step 4 can be recovered and reused.

[0044] As a second aspect of the present invention, a method for preparing a high thermal conductivity polytetrafluoroethylene ceramic composite membrane is also provided. Different from the above-mentioned method for preparing a polytetrafluoroethylene ceramic composite membrane, the inorganic filler powder in the components provided by the method for preparing a high thermal conductivity polytetrafluoroethylene ceramic composite membrane must meet the following requirements: the inorganic filler powder is a mixed filler of spherical silica, spherical alumina, flaky boron nitride and spherical boron nitride.

[0045] Preferably, the amount of the mixed filler is 50 vol% to 75 vol% of the total volume of the fluororesin and the filler.

[0046] Preferably, the amount of the mixed filler is 55 vol% to 65 vol% of the total volume of the fluororesin and the filler.

[0047] Preferably, the particle size of the spherical silica and spherical alumina is 1-5 μm.

[0048] Preferably, the flake particles of the flake boron nitride have a particle size of 10-20 μm.

[0049] Preferably, the particle size of the spherical boron nitride is 50-100 μm.

[0050] Preferably, the inorganic filler powder is a filler powder surface-treated with a silane coupling agent.

[0051] Preferably, with the total volume of the mixed filler being 100 parts, the volume ratio of spherical boron nitride is 10-20 vol%, the volume ratio of flaky boron nitride is 15-30 vol%, and the volume ratio of the total amount of spherical silica and spherical alumina is 50-75 vol%; spherical silica and spherical alumina in the mixed filler are mixed in any proportion.

[0052] As a second aspect of the present invention, an application of a high thermal conductivity polytetrafluoroethylene ceramic composite film is also provided for preparing a high thermal conductivity high frequency copper clad laminate. The high thermal conductivity polytetrafluoroethylene ceramic composite film prepared according to the above preparation method is cut, one or more layers are stacked, copper foil is coated on both sides or one side, and laminated in a vacuum high temperature press to obtain the high thermal conductivity high frequency copper clad laminate.

[0053] Preferably, the thermal conductivity of the high thermal conductivity high frequency copper clad laminate with a thickness of 1.0 mm is not less than 1.2 W / (m•K).

[0054] Preferably, the temperature of the high temperature lamination is 350-400°C.

[0055] The "high thermal conductivity" in the present invention means that according to the ASTM D5470 method, using the standard heat flow method, the thermal conductivity of the hard copper clad laminate substrate with a test medium thickness of 1.0 mm is not less than 1.2 W / (m•K).

[0056] The invention also discloses a method for preparing modified polytetrafluoroethylene, comprising: using 1-allylhydantoin to carry out a grafting reaction with polytetrafluoroethylene to obtain the modified polytetrafluoroethylene.

[0057] The invention adopts 1-allylhydantoin as a modifier to graft-modify polytetrafluoroethylene, and then uses the modified polytetrafluoroethylene for preparing a polytetrafluoroethylene ceramic membrane, so that the obtained polytetrafluoroethylene ceramic membrane has good density and tensile strength.

[0058] Specifically, the preparation method of the modified polytetrafluoroethylene comprises the following steps:

[0059] Polytetrafluoroethylene in 60 The polytetrafluoroethylene after irradiation is irradiated with 45-55 kGy of gamma rays in a Co radiation source, and then the irradiated polytetrafluoroethylene is added to a mixture of ethanol and distilled water, and then 1-allylhydantoin, ammonium ferrous sulfate and concentrated sulfuric acid with a concentration of 90-95 wt% are added. Under a nitrogen atmosphere, the temperature is raised to 60-70° C., the reaction is carried out for 4-7 hours, the mixture is filtered, Soxhlet extraction is carried out for 55-65 hours, and the mixture is dried to obtain modified polytetrafluoroethylene.

[0060] Preferably, the mass volume ratio of the above-mentioned polytetrafluoroethylene to the mixed solution is 1g:15-20mL; the volume ratio of ethanol to distilled water is 1:2-3; the concentration of 1-allylhydantoin in the mixed solution is 20-30wt%; the concentration of ammonium ferrous sulfate in the mixed solution is 0.08-0.15g / L; and the concentration of concentrated sulfuric acid in the mixed solution is 0.7-1.3mL / L.

[0061] Beneficial effects of the present invention:

[0062] 1. Compared with the extrusion and calendering production process used in the existing solvent-based polytetrafluoroethylene ceramic-based high-frequency board, the present invention adopts a coating process, a step-by-step volatilization of the solvent, and a step-by-step continuous hot calendering, that is, a coating method is used to prepare the polytetrafluoroethylene ceramic green film, and the green film is subjected to a step-by-step "heat treatment-hot calendering" treatment, thereby realizing the continuous roll production of the polytetrafluoroethylene ceramic film;

[0063] 2. Compared with the existing production process of water-based polytetrafluoroethylene ceramic composite membranes, the present invention adopts a continuous hot calendering method to gradually increase the material density, eliminate film-forming defects, and avoid the defects of micropores and voids on the membrane surface caused by the existing water-based emulsion coating-sintering process; the prepared composite membrane has uniform density and thickness, and its tensile strength is better than that of the composite membrane produced by the existing water-based emulsion coating process;

[0064] 3. The method of the present invention can obtain a polytetrafluoroethylene ceramic composite film with high thermal conductivity and high filler content and a high-frequency copper-clad laminate material with high thermal conductivity; and has high thermal conductivity and low dielectric loss characteristics at high frequencies, and is suitable for high-power, high-frequency, and high-speed printed circuit board products with high requirements for thermal management. BRIEF DESCRIPTION OF THE DRAWINGS

[0065] Figure 1 These are the infrared spectrum test results of the modified polytetrafluoroethylene and polytetrafluoroethylene prepared in Example 8. DETAILED DESCRIPTION

[0066] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0067] The raw materials used are listed below:

[0068] Japan Daikin, polytetrafluoroethylene resin powder, brand M-18F, particle size 25μm.

[0069] Shandong Dongyue, polytetrafluoroethylene suspension fine powder, brand DF-162, particle size 20-30μm.

[0070] 3M Company, USA, PFA resin powder, brand name Dyneon PFA 6503PAZ, particle size 30μm.

[0071] 3M Company, USA, FEP resin powder, brand name Dyneon FEP 6322PAZ, particle size 5μm.

[0072] Jiangsu Lianrui New Materials Co., Ltd., spherical silica powder, particle size 2-4μm.

[0073] Shandong National Ceramics, titanium dioxide powder, particle size 1-10μm.

[0074] Shaanxi Walter New Materials, high silica glass chopped fibers, diameter 0.9-3μm, customizable length.

[0075] BYK company, rheological additive, brand name RHEOBYK-410.

[0076] Mixed xylene, commercially available.

[0077] ExxonMobil Corporation, aromatic solvent, brand Solvesso 100.

[0078] Jiangsu Hualun Company, aromatic solvent, brand name Galasol S-100B.

[0079] ExxonMobil, aromatic solvent, brand Solvesso 200ND.

[0080] Jiangsu Hualun Company, aromatic solvent, brand name Galasol S-200.

[0081] The filler purchased in the embodiment of the present invention is filler powder surface-treated with a silane coupling agent.

[0082] Example 1

[0083] In this embodiment, a method for preparing a polytetrafluoroethylene ceramic composite membrane is first provided, comprising the following steps:

[0084] Step 1, 92 parts by weight of PTFE powder (brand name M-18F), 8 parts by weight of PFA resin powder, 0.2 parts by weight of rheological additive, 30 parts by weight of mixed xylene, 20 parts by weight of Solvesso 100 aromatic solvent, 10 parts by weight of Solvesso 200ND aromatic solvent, and spherical silica powder (the amount of spherical silica powder accounts for 63 vol% of the total volume of fluororesin and filler), and stir and mix at high speed for 1 hour to obtain a uniformly dispersed emulsion;

[0085] Step 2, the above glue solution is coated on the surface of the polyimide film by a horizontal coating machine, the oven segment temperature is 80, 90, 120, 130, 120 ° C, the speed is uniform, the total residence time is 3 minutes, and a tetrafluoroethylene glue-coated PI film with a coating thickness of 150 μm is obtained;

[0086] Step 3, unwinding, hot pressing, and winding the above-mentioned coated film on a continuous hot press, the surface temperature of the hot pressing roller is 95°C, the calendering line speed is 1.0m / min, the calendering roller top pressure is 25t, and the micropores in the membrane material are eliminated through the hot pressing operation to obtain a polytetrafluoroethylene ceramic membrane coil with a composite PI membrane and a high-boiling point aromatic solvent having a glue layer thickness of 140μm;

[0087] Step 4, passing the coil through a ventilated oven for baking to volatilize the high boiling point solvent therein; the oven temperature is set in stages, and the five temperatures are: 220, 240, 260, 260, 220°C, passing at an average speed, and the total residence time is 7 minutes;

[0088] Step 5, subjecting the coiled material treated in step 4 to a second hot pressing treatment on a continuous hot press, with a roller surface temperature of 110° C., a calendering line speed of 1.5 m / min, and a calendering roller top pressure of 25 t, to obtain a polytetrafluoroethylene ceramic membrane coiled material with a composite PI membrane and a glue layer thickness of 127 μm;

[0089] Step 6: sinter the coiled material in step 5 in a high temperature oven at a sintering temperature of 350° C. for 10 min. After cooling, peel off the PI film and roll it up to obtain a polytetrafluoroethylene ceramic composite film coiled material.

[0090] In this embodiment, a method for preparing a polytetrafluoroethylene ceramic-based high-frequency copper-clad laminate is also provided.

[0091] Four 127μm thick polytetrafluoroethylene ceramic films were stacked, and both sides were covered with 1oz thick copper foil, and then continuously laminated in a vacuum hot press. The lamination temperature was 380℃, the lamination pressure was 4.0MPa, and the maximum temperature holding time was 2h, resulting in a polytetrafluoroethylene ceramic-based high-frequency copper-clad laminate with a dielectric thickness of 0.508mm.

[0092] Example 2

[0093] The preparation steps of Example 2 are different from those of Example 1 in that the PFA resin powder is replaced with FEP resin powder, namely:

[0094] Step 1, 92 parts by weight of PTFE powder (brand name M-18F), 8 parts by weight of FEP resin powder, 0.2 parts by weight of rheological additive, 30 parts by weight of mixed xylene, 20 parts by weight of Solvesso 100 aromatic solvent, 10 parts by weight of Solvesso 200ND aromatic solvent, and spherical silica powder (the amount of spherical silica powder accounts for 63 vol% of the total volume of fluororesin and filler), and stir and mix at high speed for 1 hour to obtain a uniformly dispersed emulsion;

[0095] The other steps are the same, and a 127 μm thick polytetrafluoroethylene ceramic composite membrane coil is prepared; and a 0.508 mm medium thickness polytetrafluoroethylene ceramic-based copper-clad laminate is prepared.

[0096] Example 3

[0097] The preparation steps of Example 3 are different from those of Example 1, in that the PFA resin powder is replaced with a mixture of FEP resin powder and PFA resin powder in a ratio of 1:1 by weight, namely:

[0098] Step 1, 92 parts by weight of PTFE powder (brand name M-18F), 4 parts by weight of PFA resin powder, 4 parts by weight of FEP resin powder, 0.2 parts by weight of rheological additive, 30 parts by weight of mixed xylene, 20 parts by weight of Solvesso 100 aromatic solvent, 10 parts by weight of Solvesso 200ND aromatic solvent, and spherical silica powder (the amount of spherical silica powder accounts for 63 vol% of the total volume of fluororesin and filler) are stirred and mixed at high speed for 1 hour to obtain a uniformly dispersed emulsion.

[0099] The other steps are the same, and a 127 μm thick polytetrafluoroethylene ceramic composite membrane coil is prepared; and a 0.508 mm medium thickness polytetrafluoroethylene ceramic-based copper-clad laminate is prepared.

[0100] Example 4

[0101] The preparation steps of Example 4 are different from those of Example 1 in that the fluororesin is only PTFE resin powder, namely:

[0102] Step 1. Mix 100 parts by weight of PTFE suspended fine powder (brand name DF-162), 0.2 parts by weight of rheological additive, 30 parts by weight of mixed xylene, 20 parts by weight of Galasol S-100B aromatic solvent, 10 parts by weight of Galasol S-200 aromatic solvent, and spherical silica powder (the amount of spherical silica powder accounts for 63 vol% of the total volume of fluororesin and filler) with high-speed stirring for 1 hour to obtain a uniformly dispersed emulsion.

[0103] The other steps are the same, and a 127 μm thick polytetrafluoroethylene ceramic composite membrane coil is prepared; and a 0.508 mm medium thickness polytetrafluoroethylene ceramic-based copper-clad laminate is prepared.

[0104] Example 5

[0105] In this embodiment, a method for preparing a polytetrafluoroethylene ceramic composite film roll with a thickness of 63 μm is provided.

[0106] Step 1, 92 parts by weight of PTFE powder (brand name M-18F), 8 parts by weight of FEP resin powder, 0.2 parts by weight of rheological additive, 30 parts by weight of mixed xylene, 20 parts by weight of Solvesso 100 aromatic solvent, 10 parts by weight of Solvesso 200ND aromatic solvent, and spherical silica powder (the amount of spherical silica powder accounts for 63 vol% of the total volume of fluororesin and filler), and stir and mix at high speed for 0.5 h to obtain a uniformly dispersed emulsion, then add the above-mentioned dispersed emulsion into a ball mill, and high-speed ball mill for 3 h under cooling to obtain a uniformly dispersed fine particle emulsion;

[0107] Step 2, the above-mentioned ground glue liquid is coated on the surface of the polyimide film by a horizontal coating machine, the oven segment temperature is 80, 90, 120, 130, 120 ° C, the speed is uniform, the total residence time is 4 minutes, and a tetrafluoroethylene glue PI film with a coating thickness of 75 μm is obtained;

[0108] Step 3: Unwind, hot press, and rewind the above-mentioned coated film on a continuous hot press, with the hot press roller surface temperature of 95°C, the calendering line speed of 1.0 m / min, and the top pressure of 30t. Through the hot press operation, the micropores in the membrane material are eliminated to obtain a polytetrafluoroethylene ceramic membrane coil with a composite PI membrane and a high-boiling-point aromatic solvent having a glue layer thickness of 66μm;

[0109] Step 4: Pass the coil through a ventilated oven to bake and volatilize the high boiling point solvent. The oven temperature is set in stages, with five stages of temperature: 220, 240, 260, 260, 220°C, with an average speed and a total residence time of 7 minutes;

[0110] Step 5, subjecting the coiled material treated in step 4 to a second hot pressing treatment on a continuous hot pressing machine, with a hot pressing roller surface temperature of 120°C, a calendering line speed of 1.5m / min, and a top pressure of 35t, to obtain a polytetrafluoroethylene ceramic membrane coiled material with a composite PI membrane and a glue layer thickness of 63μm;

[0111] Step 6: The coil is sintered in a high-temperature oven at a temperature of 350° C. for 30 min. After cooling, the PI film is peeled off and rolled up to obtain a polytetrafluoroethylene ceramic composite film coil.

[0112] In this embodiment, a method for preparing a polytetrafluoroethylene ceramic-based copper-clad laminate is also provided.

[0113] Four 63μm thick polytetrafluoroethylene ceramic films were stacked, and both sides were covered with 1 / 2oz thick copper foil, and laminated in a vacuum hot press. The lamination temperature was 380℃, the lamination pressure was 4.0MPa, and the maximum temperature holding time was 1h. A polytetrafluoroethylene ceramic-based copper-clad laminate with a dielectric thickness of 0.25mm was obtained.

[0114] Example 6

[0115] In this embodiment, a method for preparing a polytetrafluoroethylene ceramic composite film roll is provided.

[0116] Step 1, 92 parts by weight of PTFE powder (brand name M-18F), 8 parts by weight of PFA resin powder, 0.2 parts by weight of rheological additive, 30 parts by weight of mixed xylene, 20 parts by weight of Solvesso 100 aromatic solvent, 10 parts by weight of Solvesso 200ND aromatic solvent, spherical silica powder (the amount of spherical silica powder accounts for 9.5 vol% of the total volume of fluororesin and filler), titanium dioxide powder (the amount of titanium dioxide powder accounts for 40.5 vol% of the total volume of fluororesin and filler), and mix them at high speed for 2 hours to obtain a uniformly dispersed emulsion;

[0117] Step 2, coating the above glue solution on the surface of aluminum foil by a horizontal coating machine, with the oven segment temperatures of 80, 90, 120, 130, and 120° C., passing through at an even speed, with a total residence time of 4 min, to obtain a polytetrafluoroethylene glue-coated aluminum foil with a coating thickness of 125 μm;

[0118] Step 3, unwinding, hot pressing, and rewinding the above-mentioned coated foil on a hot press, the surface temperature of the hot pressing roller is 100° C., the calendering line speed is 1.0 m / min, and the top pressure is 25 t. Through the hot pressing operation, the micropores in the membrane material are eliminated to obtain a polytetrafluoroethylene ceramic membrane coil with a composite PI membrane and a high-boiling-point aromatic hydrocarbon solvent having a glue layer thickness of 115 μm;

[0119] Step 4: Pass the coil through a ventilated oven to bake and volatilize the high boiling point solvent. The oven temperature is set in stages, with five stages of temperature: 220, 240, 260, 260, 220°C, with an average speed and a total residence time of 7 minutes;

[0120] Step 5, subjecting the coiled material treated in step 4 to a second hot pressing treatment on a continuous hot pressing machine, with a hot pressing roller surface temperature of 105° C., a calendering line speed of 1.5 m / min, and a top pressure of 25 t, to obtain a polytetrafluoroethylene ceramic membrane coiled material with a glue layer thickness of 101 μm;

[0121] Step 6: The coil is sintered in a high-temperature oven at a temperature of 350° C. for 10 min. After cooling, the aluminum foil is peeled off and the coil is rolled up to obtain the polytetrafluoroethylene ceramic composite membrane coil.

[0122] In this embodiment, a method for preparing a polytetrafluoroethylene ceramic-based copper-clad laminate is also provided.

[0123] Five 101μm thick polytetrafluoroethylene ceramic films were stacked, and both sides were covered with 1 / 2oz thick copper foil, and laminated in a vacuum hot press. The lamination temperature was 370℃, the lamination pressure was 6.0MPa, and the maximum temperature holding time was 1h. A polytetrafluoroethylene ceramic-based copper-clad laminate with a dielectric thickness of 0.508 mm was obtained.

[0124] Example 7

[0125] In this embodiment, a method for preparing a chopped glass fiber reinforced polytetrafluoroethylene composite film roll is provided.

[0126] Step 1, 90 parts by weight of PTFE powder (brand name M-18F), 10 parts by weight of FEP resin powder, 0.5 parts by weight of rheological additive, 50 parts by weight of mixed xylene, 30 parts by weight of Solvesso 100 aromatic solvent, 10 parts by weight of Solvesso 200ND aromatic solvent, and short-cut high-silica glass fiber (length less than 3 mm, the amount of short-cut high-silica glass fiber accounts for 5 vol% of the total volume of fluororesin and filler), are dispersed and mixed at high speed for 2 hours to obtain a uniformly dispersed emulsion;

[0127] Step 2, coating the above glue solution on the surface of aluminum foil by a horizontal coating machine, with the oven segment temperatures of 80, 90, 120, 130, and 120° C., passing through at an even speed, with a total residence time of 7 min, to obtain a polytetrafluoroethylene glue-coated aluminum foil with a coating thickness of 135 μm;

[0128] Step 3, unwinding, hot pressing, and rewinding the above-mentioned coated foil on a hot pressing machine, with the surface temperature of the hot pressing roller being 100° C., the line speed being 1.0 m / min, and the top pressure being 25 t. Through the hot pressing operation, micropores in the membrane material are eliminated to obtain a glass fiber reinforced polytetrafluoroethylene membrane coil with a glue layer thickness of 130 μm and containing a high-boiling point aromatic hydrocarbon solvent;

[0129] Step 4: Pass the coil through a ventilated oven to bake and volatilize the high boiling point solvent. The oven temperature is set in stages, with five stages of temperature: 220, 240, 260, 260, 220°C, with an average speed and a total residence time of 7 minutes;

[0130] Step 5, subjecting the coiled material treated in step 4 to a second hot pressing treatment on a continuous hot pressing machine, with a hot pressing roller surface temperature of 120° C., a calendering line speed of 1.5 m / min, and a top pressure of 25 t, to obtain a chopped glass fiber reinforced polytetrafluoroethylene film coiled material with a glue layer thickness of 127 μm;

[0131] Step 6: The coil is sintered in a high-temperature oven at a temperature of 350° C. for 10 min. After cooling, the coil is peeled off and rolled up to obtain the chopped random glass fiber reinforced polytetrafluoroethylene composite film coil.

[0132] In this embodiment, a method for preparing a polytetrafluoroethylene ceramic-based copper-clad laminate is also provided.

[0133] A 127μm thick chopped glass fiber polytetrafluoroethylene film was coated with 1 / 2oz thick copper foil on both sides and laminated in a vacuum hot press. The lamination temperature was 380℃, the lamination pressure was 4.0MPa, and the maximum temperature holding time was 1h. A chopped glass fiber reinforced polytetrafluoroethylene copper clad laminate with a dielectric thickness of 0.127mm was obtained.

[0134] Example 8

[0135] The difference between a method for preparing a polytetrafluoroethylene ceramic composite membrane and Example 1 is that modified polytetrafluoroethylene is used instead of polytetrafluoroethylene (PTFE powder).

[0136] The difference between a method for preparing a polytetrafluoroethylene ceramic-based high-frequency copper-clad laminate and Example 1 is that the polytetrafluoroethylene ceramic composite film prepared in this example is used for preparation.

[0137] The preparation method of modified polytetrafluoroethylene comprises the following steps:

[0138] Polytetrafluoroethylene in 60 The polytetrafluoroethylene was irradiated with 48 kGy of gamma rays in a Co radiation source, and then the irradiated polytetrafluoroethylene was added to a mixture of ethanol and distilled water, and then 1-allylhydantoin, ammonium ferrous sulfate and concentrated sulfuric acid with a concentration of 93 wt% were added. The temperature was raised to 68 ° C under a nitrogen atmosphere, and the reaction was carried out for 6 hours. The mixture was filtered, extracted with Soxhlet for 58 hours, and dried to obtain modified polytetrafluoroethylene. The mass volume ratio of the polytetrafluoroethylene to the mixture was 1 g: 15 mL; the volume ratio of ethanol to distilled water was 1: 2; the concentration of 1-allylhydantoin in the mixture was 20 wt%; the concentration of ammonium ferrous sulfate in the mixture was 0.08 g / L; and the concentration of concentrated sulfuric acid in the mixture was 0.7 mL / L.

[0139] The modified polytetrafluoroethylene and polytetrafluoroethylene prepared above were tested by infrared spectroscopy, and the results were as follows: Figure 1 As shown. Figure 1 It can be seen that compared with the infrared spectrum of polytetrafluoroethylene, the infrared spectrum of modified polytetrafluoroethylene is at 1663cm -1 There is an infrared characteristic absorption peak of C=O bond at 1573cm -1 The presence of the infrared characteristic absorption peak of NH bond at , indicates that 1-allylhydantoin participates in the formation reaction of modified polytetrafluoroethylene.

[0140] The polytetrafluoroethylene ceramic composite film coils prepared in Examples 1-8 have uniform thickness, dense appearance, sufficient tensile strength and tear strength, and can be rolled, unrolled, cut, etc. on mechanical equipment. The copper clad laminates prepared in Examples 1-8 have a size of 18 inches by 24 inches. Ten sheets are taken from the same batch for testing. According to the IPC-TM-650 standard test method for high-frequency copper clad laminates, the dielectric thickness, thickness tolerance, dielectric constant, dielectric loss, and CTE are tested.

[0141] Table 1 Performance test results of copper clad laminates prepared in Examples 1-8

[0142]

[0143] It can be seen from Table 1 that the copper clad laminates prepared in Examples 1-8 have the advantages of good thickness uniformity, dielectric loss less than 0.0030, low thermal expansion coefficient, etc., and can be used for high-frequency and high-speed circuit boards.

[0144] It can be seen from Example 5 that the technology described in the present invention can coat a uniform ceramic film with a minimum thickness of 60 μm, and the performance is no different from that of a high-frequency board pressed with a 127 μm ceramic film.

[0145] It can be seen from Example 6 that the technology described in the present invention can prepare a polytetrafluoroethylene copper clad laminate with a high dielectric constant by changing the type and amount of filler added.

[0146] It can be seen from Example 7 that the technology described in the present invention can also be applied to fibrous fillers. By adding a small amount of chopped fibers, a high-frequency copper-clad laminate with a dielectric constant of about 2.20 can be obtained. Compared with pure PTFE sheet material (thermal expansion coefficient of 230-250ppm / ℃), the z-axis thermal expansion coefficient of the copper-clad laminate prepared in Example 7 is significantly reduced.

[0147] The relative density and tensile properties of the polytetrafluoroethylene ceramic membranes obtained in Examples 1-4 and Example 8 were tested, and their surface morphologies were observed under a microscope.

[0148] Table 2 Performance test results of polytetrafluoroethylene ceramic membranes obtained in Examples 1-4 and Example 8

[0149]

[0150] From the results in Table 2, it can be seen that Examples 1-3 contain a certain amount of FEP resin and PFA resin. Compared with Example 4, due to the fluidity of FEP resin and PFA resin, the density of the ceramic film is slightly higher, the tensile strength is better, and the surface morphology is better. Therefore, a certain amount of FEP resin or PFA resin has a positive effect on improving the mechanical properties and surface defects of the ceramic film. There is no significant difference in the basic properties of the prepared copper clad laminate.

[0151] In addition, it can be seen from Table 2 that compared with Example 1, the density and tensile strength of Example 8 are improved, indicating that the ceramic composite membrane prepared by using modified polytetrafluoroethylene instead of polytetrafluoroethylene has good density and tensile strength.

[0152] Comparative Example 1

[0153] The preparation steps of Comparative Example 1 are compared with those of Example 1, wherein the addition amount of PFA resin powder is 30 parts by weight, and the addition amount of PTFE powder is 70 parts by weight, namely:

[0154] Step 1: 70 parts by weight of PTFE powder (brand name M-18F), 30 parts by weight of PFA resin powder, 0.2 parts by weight of rheological additive, 30 parts by weight of mixed xylene, 20 parts by weight of Solvesso 100 aromatic solvent, 10 parts by weight of Solvesso 200ND aromatic solvent, and spherical silica powder (the amount of spherical silica powder accounts for 63.1 vol% of the total volume of fluororesin and filler) are mixed at high speed for 1 hour to obtain a uniformly dispersed emulsion.

[0155] The other steps are the same, and a 127 μm thick polytetrafluoroethylene ceramic composite membrane coil is prepared; and a 0.508 mm medium thickness polytetrafluoroethylene ceramic-based copper-clad laminate is prepared.

[0156] The copper clad laminate obtained in Comparative Example 1 was tested for its dielectric constant, dielectric loss, and CTE according to the standard test method for high-frequency copper clad laminates in IPC-TM-650.

[0157] Table 3 Performance test results of copper clad laminate obtained in Comparative Example 1

[0158]

[0159] By comparing Examples 1-4 with Comparative Example 1, it can be seen from Table 3 that if the amount of PFA added is too high, the dielectric loss of the prepared copper clad laminate will increase significantly. However, there is no significant change in the dielectric constant and the thermal expansion coefficient. This indicates that there is an upper limit to the amount of PFA or FEP resin powder added. After experimental verification, in the scheme described in the present invention, preferably, the weight of the polytetrafluoroethylene resin powder is not less than 85 parts based on 100 parts by weight of all fluororesin powders.

[0160] Comparative Example 2

[0161] In this comparative example, aqueous polytetrafluoroethylene emulsion was used to prepare polytetrafluoroethylene ceramic membrane and copper clad laminate.

[0162] The raw materials used in this comparative example are as follows:

[0163] Polytetrafluoroethylene concentrated aqueous emulsion, brand DF-304, solid content 60wt%;

[0164] FEP water emulsion, brand ND-4R, solid content 39%;

[0165] Spherical silica powder, particle size 2-4μm;

[0166] RHEOBYK-7600 water-based thickener, 15% aqueous solution.

[0167] The preparation steps of this comparative example are as follows:

[0168] Take 150 parts by weight of the above-mentioned polytetrafluoroethylene aqueous emulsion, 25.6 parts by weight of FEP aqueous emulsion, 1.0 part by weight of thickener, and spherical silica powder (the amount of spherical silica powder accounts for 63.2 vol% of the total volume of fluororesin and filler), mix for 2 hours, then add deionized water and adjust the viscosity to 700 mPa•s to obtain a polytetrafluoroethylene ceramic composite aqueous slurry.

[0169] The slurry is horizontally coated on the surface of the polyimide base film, and the oven temperature is set at 85°C in stages to obtain a 130μm thick polytetrafluoroethylene ceramic PI film. The obtained raw film is pre-burned in a high-temperature tunnel ventilation oven to discharge small organic molecules, and the oven temperature is set at 260°C in stages. Subsequently, it is sintered at 350°C in a high-temperature oven for 15 minutes to form a dense polytetrafluoroethylene ceramic composite film. Finally, after cooling, the PI film is peeled off to obtain a polytetrafluoroethylene ceramic composite film coil with a thickness of 127μm.

[0170] The above four 127μm thick polytetrafluoroethylene ceramic films were stacked, and both sides were covered with 1oz thick copper foil, and laminated in a vacuum hot press. The lamination temperature was 380℃, the lamination pressure was 4.0MPa, and the maximum temperature holding time was 2h. A polytetrafluoroethylene ceramic-based copper-clad laminate with a dielectric thickness of 0.508 mm was obtained.

[0171] The relative density and tensile properties of the polytetrafluoroethylene ceramic membrane obtained in Comparative Example 2 were tested, and its surface morphology was observed under a microscope.

[0172] Table 4 Performance test results of polytetrafluoroethylene ceramic membrane obtained in Comparative Example 2

[0173]

[0174] By comparing Examples 1-4 with Comparative Example 2, it can be seen from Table 4 that the polytetrafluoroethylene ceramic membrane prepared by the aqueous emulsion has a low relative density and a significant increase in apparent defects. Due to the large number of surface defects, the ceramic membrane obtained by the aqueous method has a low tensile strength and a reduced elongation at break. Therefore, in actual operation, the polytetrafluoroethylene ceramic membrane coil obtained by the aqueous slurry coating-sintering method needs to be carefully handled during winding, unwinding and cutting operations to control tension and avoid tearing.

[0175] The copper clad laminate prepared in Comparative Example 2 has a size of 18 inches by 24 inches. Ten sheets are selected from the same batch for testing. According to the IPC-TM-650 standard test method for high-frequency copper clad laminates, the dielectric thickness, thickness tolerance, dielectric constant, dielectric loss, and CTE are tested.

[0176] Table 5 Performance test results of copper clad laminate prepared in Comparative Example 2

[0177]

[0178] By comparing the copper clad laminates prepared in Examples 1-4 with Comparative Example 2, it can be seen from Table 5 that due to the poor film thickness control of the aqueous emulsion prepared in Comparative Example 2 during the continuous coating process, the thickness of the film materials produced before and after are greatly different after being hot-pressed into copper clad laminates, and the dielectric thickness tolerance of the same batch of materials prepared is large. In addition, due to the presence of microscopic defects in the film prepared in Comparative Example 2, the dielectric constant of the material is reduced and the dielectric loss is slightly higher.

[0179] It can be seen that the technical solution described in the present invention can effectively eliminate film-forming defects and avoid defects such as micropores and voids in the existing process compared with the currently reported water-based emulsion coating technical solution; the prepared composite film has good thickness uniformity; and the tensile breaking strength is better than the water-based emulsion coating process.

[0180] Comparative Example 3

[0181] In Comparative Example 3, the polytetrafluoroethylene membrane was attempted to be prepared without adding a high-boiling point aromatic hydrocarbon solvent to the slurry.

[0182] Step 1, 92 parts by weight of PTFE powder (brand name M-18F), 8 parts by weight of PFA resin powder, 0.2 parts by weight of rheological additive, 30 parts by weight of mixed xylene, 30 parts by weight of Solvesso 100 aromatic solvent, and spherical silica powder (the amount of spherical silica powder accounts for 63.2 vol% of the total volume of fluororesin and filler), are stirred and mixed at high speed for 1 hour to obtain a uniformly dispersed emulsion;

[0183] Step 2, the above glue solution is coated on the surface of the polyimide film by a horizontal coating machine, the oven segment temperature is 80, 90, 120, 130, 120 ° C, the speed is uniform, the total residence time is 3 minutes, and a tetrafluoroethylene glue-coated PI film with a coating thickness of 135 μm is obtained;

[0184] Step 3, unwinding, hot pressing and winding the above-mentioned adhesive film on a continuous hot calender, the surface temperature of the hot pressing roller is 95°C, the calendering line speed is 1.0m / min, and the top pressure is 25t;

[0185] Step 4: pass the coil through a ventilated oven for baking at a temperature of 260° C. for a residence time of 7 min;

[0186] Step 5: The coil is sintered in a high-temperature oven at a temperature of 350° C. for 10 min. After cooling, the PI film is peeled off to obtain a polytetrafluoroethylene ceramic film.

[0187] The polytetrafluoroethylene ceramic membrane prepared in Comparative Example 3 has many surface cracks and poor strength. In step 5, it is difficult to completely peel off from the surface of the PI base film. As can be seen from Comparative Example 3, in the method of the present invention, a high-boiling point aromatic hydrocarbon solvent is necessary, especially the combination of high / low boiling point aromatic hydrocarbon solvents and the formation of step-by-step volatilization. The single "coating-baking-sintering" process of polytetrafluoroethylene solvent-based emulsion cannot obtain a polytetrafluoroethylene ceramic membrane roll with a dense surface.

[0188] Comparative Example 4

[0189] In Comparative Example 4, compared with Example 1, the hot calendering operations described in Step 3 and Step 5 were removed to attempt to prepare a polytetrafluoroethylene film.

[0190] Step 1, 92 parts by weight of PTFE powder (brand name M-18F), 8 parts by weight of PFA resin powder, 0.2 parts by weight of rheological additive, 30 parts by weight of mixed xylene, 20 parts by weight of Solvesso 100 aromatic solvent, 10 parts by weight of Solvesso 200ND aromatic solvent, and spherical silica powder (the amount of spherical silica powder accounts for 63.2 vol% of the total volume of fluororesin and filler), and stir and mix at high speed for 1 hour to obtain a uniformly dispersed emulsion;

[0191] Step 2, the above glue solution is coated on the surface of the polyimide film by a horizontal coating machine, the oven segment temperature is 80, 90, 120, 130, 120 ° C, the speed is uniform, the total residence time is 3 minutes, and a tetrafluoroethylene glue-coated PI film with a coating thickness of 150 μm is obtained;

[0192] Step 3: Pass the coil through a ventilated oven to bake and volatilize the high boiling point solvent. The oven temperature is set in stages, with five stages of temperature: 220, 240, 260, 260, 220°C, with an average speed and a total residence time of 7 minutes;

[0193] Step 4: the coil is sintered in a high temperature oven at a temperature of 350° C. for 10 min. After cooling, the PI film is peeled off to obtain a polytetrafluoroethylene ceramic composite film.

[0194] For the polytetrafluoroethylene ceramic membrane obtained in Comparative Example 4, its relative density and tensile properties were tested, and its surface morphology was observed.

[0195] Table 6 Performance test results of polytetrafluoroethylene ceramic membrane obtained in Comparative Example 4

[0196]

[0197] As shown in Table 6, the polytetrafluoroethylene ceramic film prepared in Comparative Example 4 has visible cracks on the surface, the film strength is poor, and it is difficult to roll in step 4. As shown in the results of the above table, compared with Examples 1-4, the film prepared in Comparative Example 4 has no continuous hot calendering step, the density is greatly reduced, the tensile strength is low, and the apparent defects are obvious. This shows that the continuous hot calendering step of the present invention is necessary, especially the step-by-step continuous hot calendering.

[0198] Example 9

[0199] Example 9 provides a method for preparing a high thermal conductivity polytetrafluoroethylene-based copper clad laminate.

[0200] The raw materials that are different between this embodiment and the previous embodiment are listed as follows:

[0201] Spherical alumina, model BAK5, particle size D50 = 5-6 μm;

[0202] Quasi-spherical alumina, model NSM-1S, particle size D50 = 0.8 μm;

[0203] Spherical boron nitride, model GBN-60, particle size D50 = 60-75μm;

[0204] Flake boron nitride, model ABN-15, particle size D50=12-13μm.

[0205] The preparation method of high thermal conductivity polytetrafluoroethylene ceramic film is as follows:

[0206] Step 1: 90 parts by weight of PTFE powder (brand name M-18F), 10 parts by weight of FEP resin powder, 0.5 parts by weight of rheological additive, 60 parts by weight of mixed xylene, 40 parts by weight of Solvesso 100 aromatic solvent, 20 parts by weight of Solvesso 200ND aromatic solvent, spherical silica powder (the amount of spherical silica powder accounts for 19 vol% of the total volume of fluororesin and filler), spherical boron nitride (the amount of spherical boron nitride accounts for 12 vol% of the total volume of fluororesin and filler), flaky boron nitride (the amount of flaky boron nitride accounts for 9.5 vol% of the total volume of fluororesin and filler), and alumina (the amount of alumina accounts for 19.5 vol% of the total volume of fluororesin and filler) are mixed under high-speed stirring for 1 hour to obtain a uniformly dispersed emulsion;

[0207] Step 2, the above glue solution is coated on the surface of the polyimide film by a horizontal coating machine, the oven segment temperature is 80, 100, 120, 130, 120 ° C, the speed is uniform, the total residence time is 5 minutes, and a tetrafluoroethylene glue-coated PI film with a coating thickness of 150 μm is obtained;

[0208] Step 3, unwinding, hot pressing, and winding the above-mentioned coated film on a hot pressing machine, the surface temperature of the hot pressing roller is 95° C., the calendering line speed is 1.5 m / min, and the top pressure is 25 t. Through the hot pressing operation, the micropores in the membrane material are eliminated to obtain a polytetrafluoroethylene ceramic membrane coil with a composite PI membrane and a high-boiling point aromatic solvent having a glue layer thickness of 140 μm;

[0209] Step 4: Pass the coil through a ventilated oven to bake and volatilize the high boiling point solvent. The oven temperature is set in stages, with five stages of temperature: 220, 240, 260, 260, 220°C, with an average speed and a total residence time of 7 minutes;

[0210] Step 5, subjecting the coiled material treated in step 4 to a second hot pressing treatment on a continuous hot pressing machine, with the surface temperature of the hot pressing roller being 110° C. and the top pressure being 35 t, to obtain a polytetrafluoroethylene ceramic membrane coiled material with a composite PI membrane and a glue layer thickness of 127 μm;

[0211] Step 6: The coil is sintered in a high-temperature oven at a sintering temperature of 350° C. for 10 min. After cooling, the PI film is peeled off and rolled up to obtain the polytetrafluoroethylene ceramic composite membrane coil.

[0212] In this embodiment, a method for preparing a polytetrafluoroethylene ceramic-based copper-clad laminate is provided.

[0213] Four 127μm thick polytetrafluoroethylene ceramic films were stacked, and both sides were covered with 1oz thick copper foil, and laminated in a vacuum hot press. The lamination temperature was 380℃, the lamination pressure was 7.0MPa, and the maximum temperature holding time was 2h. A high thermal conductivity polytetrafluoroethylene ceramic-based copper-clad laminate with a dielectric thickness of 0.508mm was obtained.

[0214] Example 10

[0215] Compared with Example 9, the ratio of alumina and boron nitride thermal conductive fillers is changed in Example 10, as shown below.

[0216] Step 1, 90 parts by weight of PTFE powder (brand name M-18F), 10 parts by weight of FEP resin powder, 0.5 parts by weight of rheological additive, 60 parts by weight of mixed xylene, 40 parts by weight of Solvesso 100 aromatic solvent, 20 parts by weight of Solvesso 200ND aromatic solvent, spherical silica powder (the amount of spherical silica powder accounts for 30 vol% of the total volume of fluororesin and filler), spherical boron nitride (the amount of spherical boron nitride accounts for 20 vol% of the total volume of fluororesin and filler), and flake boron nitride (the amount of flake boron nitride accounts for 10 vol% of the total volume of fluororesin and filler), and stir and mix at high speed for 1 hour to obtain a uniformly dispersed emulsion;

[0217] The other steps are the same as those in Example 9. A high thermal conductivity polytetrafluoroethylene ceramic-based copper-clad laminate with a dielectric thickness of 0.508 mm is prepared.

[0218] Comparative Example 5

[0219] Compared with Example 9, in Comparative Example 5, samples with different volume addition amounts of thermally conductive fillers were prepared in Comparative Example 5a, Comparative Example 5b, and Comparative Example 5c, and the total volume ratio of the seasoning (i.e., the ratio of the thermally conductive filler to the total volume of the fluororesin and the filler) was 30 vol%, 40 vol%, and 75 vol%, respectively. The modified proportions are shown in Table 7:

[0220] The other proportions and steps in step 1 are the same as those in Example 9. Three kinds of high thermal conductivity polytetrafluoroethylene ceramic-based copper-clad laminates with a dielectric thickness of 0.508 mm were prepared.

[0221] Table 7 The proportions of Example 9 and Comparative Example 5a, Comparative Example 5b and Comparative Example 5c

[0222]

[0223] Comparative Example 6

[0224] Compared with Example 9, Comparative Example 6 only uses a high amount of aluminum oxide without adding boron nitride and silicon dioxide fillers, as shown below.

[0225] Step 1: 90 parts by weight of PTFE powder (brand name M-18F), 10 parts by weight of FEP resin powder, 1.0 parts by weight of rheological additive, 70 parts by weight of mixed xylene, 50 parts by weight of Solvesso 100 aromatic solvent, 20 parts by weight of Solvesso 200ND aromatic solvent, and spherical alumina filler (the amount of spherical alumina accounts for 70 vol% of the total volume of fluororesin and filler) are mixed at high speed for 1 hour to obtain a uniformly dispersed emulsion.

[0226] The other steps are the same as those in Example 9. A high thermal conductivity polytetrafluoroethylene ceramic-based copper-clad laminate with a dielectric thickness of 0.508 mm is prepared.

[0227] Comparative Example 7

[0228] Compared with Example 9, Comparative Example 7 does not use spherical boron nitride fillers, but replaces all spherical boron nitride fillers with flake boron nitride fillers. The specific steps are as follows:

[0229] Step 1, 90 parts by weight of PTFE powder (brand name M-18F), 10 parts by weight of FEP resin powder, 0.5 parts by weight of rheological additive, 60 parts by weight of mixed xylene, 40 parts by weight of Solvesso 100 aromatic solvent, 20 parts by weight of Solvesso 200ND aromatic solvent, spherical silica powder (the amount of spherical silica powder accounts for 19 vol% of the total volume of fluororesin and filler), flaky boron nitride (the amount of flaky boron nitride accounts for 21.5 vol% of the total volume of fluororesin and filler), and alumina (the amount of alumina accounts for 19.5 vol% of the total volume of fluororesin and filler), and mixing at high speed for 1 hour to obtain a uniformly dispersed emulsion;

[0230] The other steps are the same as those in Example 9. A high thermal conductivity polytetrafluoroethylene ceramic-based copper-clad laminate with a dielectric thickness of 0.508 mm is prepared.

[0231] The dielectric constant, dielectric loss and thermal conductivity of the copper clad laminates prepared in the above-mentioned Examples 9-10 and Comparative Examples 5-7 were tested.

[0232] Table 8 Performance test results of copper clad laminates prepared in Examples 9-10 and Comparative Examples 5-7

[0233] Test items unit Test Method Example 9 Example 10 Comparative Example 5a Comparative Example 5b Comparative Example 5c Comparative Example 6 Comparative Example 7 DK, 10 GHz / IPC-TM-650, 2.5.5.5 3.52 2.93 2.71 3.08 3.77 4.51 3.45 Df, 10 GHz / IPC-TM-650, 2.5.5.5 0.0023 0.0019 0.0020 0.0022 0.0025 0.0030 0.0027 Thermal conductivity, z-axis W / (m·K) ASTMD5470 1.31 1.20 0.66 0.75 1.14 0.85 1.02

[0234] It can be seen from Examples 9 and 10 that the technical solution provided by the present invention can prepare a high thermal conductivity polytetrafluoroethylene-based high-frequency board with a thermal conductivity coefficient of not less than 1.2W / (m•K). By adjusting the ratio and quantity of aluminum oxide, boron nitride, and silicon dioxide, a copper-clad board material with a dielectric constant of about 3.00-3.50 can be prepared. Its loss also meets the requirements of high-frequency boards.

[0235] By comparing the thermal conductivity of Example 9 with that of Comparative Examples 5a, 5b, and 5c, it is shown that with the increase in the volume percentage of the same proportion of fillers (30vol%-75vol%), the thermal conductivity shows a trend of first increasing and then decreasing. When the filler volume ratio is relatively low, fewer passages are formed between the thermally conductive fillers, and the thermal conductivity of the composite material is low; when the filler volume ratio is too large, the air gap between the thermally conductive fillers increases sharply, and the thermal conductivity of the composite material decreases. After experimental verification, using the thermally conductive filler and polytetrafluoroethylene resin system described in the present invention, the total volume ratio of the filler is between 50vol% and 70vol%. Preferably, it is between 55vol% and 65vol%.

[0236] Comparative Example 6 does not use boron nitride, but only adds spherical alumina as a thermally conductive filler. Even at a relatively high addition amount of thermally conductive filler, the thermal conductivity of the composite material in Comparative Example 6 is 0.85 W / (m•K). By comparing the thermal conductivity of Example 9 with that of Comparative Example 6, it is shown that the addition of boron nitride filler is necessary to achieve the target thermal conductivity value set by the present invention.

[0237] In Comparative Example 7, all spherical boron nitrides are replaced with flake boron nitrides of the same mass. Compared with Example 9, the thermal conductivity is significantly reduced, indicating that the addition of spherical boron nitride fillers significantly improves the thermal conductivity of the composite material. Therefore, the addition of spherical boron nitride fillers in the present invention is necessary.

[0238] Comparative Example 8

[0239] Compared with Example 9, this comparative example attempts to use an aqueous polytetrafluoroethylene emulsion to prepare a high thermal conductivity polytetrafluoroethylene ceramic film and a copper clad laminate.

[0240] The preparation steps of this comparative example are as follows:

[0241] Take 150 parts of polytetrafluoroethylene aqueous emulsion, 25.6 parts by weight of FEP aqueous emulsion, 1.0 parts by weight of aqueous thickener, spherical silica powder (the amount of spherical silica powder accounts for 19 vol% of the total volume of fluororesin and filler), spherical boron nitride (the amount accounts for 12 vol% of the total volume of fluororesin and filler), flaky boron nitride (the amount accounts for 9.5 vol% of the total volume of fluororesin and filler), and alumina (the amount accounts for 19.5 vol% of the total volume of fluororesin and filler), mix for 2 hours, then add deionized water, adjust the viscosity to 1000 mPa•s, and obtain a polytetrafluoroethylene ceramic composite aqueous slurry containing thermal conductive filler;

[0242] The slurry was horizontally coated on the surface of the polyimide base film, and the oven temperature was set at 80 and 100 ° C in two stages, with an average speed and a total residence time of 5 minutes to obtain a 130 μm thick tetrafluoroethylene ceramic PI film. Then, it was baked in a ventilated oven at 260 ° C. Due to severe cracking of the material after baking, the strength was too low, and the filler in some areas was separated, and further molding could not be performed.

[0243] It can be seen from Comparative Example 8 that it is difficult to prepare polytetrafluoroethylene ceramics containing a high volume ratio (60 vol%) of high thermal conductive filler using the existing aqueous polytetrafluoroethylene emulsion "coating-sintering" process.

[0244] The above description is only a preferred embodiment of the present invention, and does not limit the patent scope of the present invention. All equivalent structural changes made by using the contents of the present invention specification and drawings under the inventive concept of the present invention, or directly / indirectly applied in other related technical fields are included in the patent protection scope of the present invention.

Claims

1. A method for preparing a high thermal conductivity polytetrafluoroethylene ceramic composite film, characterized in that: The steps include: Step 1, fully mix fluororesin powder, inorganic filler powder, rheological additive and aromatic hydrocarbon mixed solvent to obtain a solvent-based emulsion; Step 2, apply the solvent-based emulsion in step 1 on the base film, perform a first baking treatment at 70-150°C, and prepare a polytetrafluoroethylene ceramic raw film coil coated on the film; Step 3, perform a first continuous hot calendering treatment at a hot pressing temperature of 80-140°C; Step 4, perform a second baking at 200-280°C; Step 5, perform a second continuous hot calendering treatment at a hot pressing temperature of 80-140°C, and obtain a polytetrafluoroethylene ceramic film coil of a composite base film; Step 6, perform sintering at 330-380°C, and obtain a polytetrafluoroethylene ceramic composite film after cooling; The fluororesin powder comprises a first component and a second component, wherein the first component is selected from at least one of polytetrafluoroethylene or modified polytetrafluoroethylene, and the second component is selected from any one or two of tetrafluoroethylene-perfluoroalkyl vinyl ether copolymer or polyperfluoroethylene propylene, wherein the weight of the first component is not less than 85 parts based on 100 parts by weight of the fluororesin powder; The aromatic hydrocarbon mixed solvent comprises one or more aromatic hydrocarbon solvents with a distillation range of 100-200° C., and one or more aromatic hydrocarbon solvents with a distillation range of 230-350° C.; The inorganic filler powder is a mixed filler of spherical silicon dioxide, spherical aluminum oxide, flaky boron nitride and spherical boron nitride, and the amount of the mixed filler accounts for 50 vol% to 75 vol% of the total volume of the fluororesin and the filler.

2. The method for preparing a high thermal conductivity polytetrafluoroethylene ceramic composite film according to claim 1, characterized in that: The method for preparing modified polytetrafluoroethylene comprises: using 1-allylhydantoin to carry out grafting reaction with polytetrafluoroethylene to obtain modified polytetrafluoroethylene.

3. The method for preparing a high thermal conductivity polytetrafluoroethylene ceramic composite film according to claim 1, characterized in that: Taking fluororesin powder as 100 parts by weight, the one or several aromatic hydrocarbon solvents with a distillation range of 100-200° C. are added in an amount of 20-70 parts by weight; the one or several aromatic hydrocarbon solvents with a distillation range of 230-350° C. are added in an amount of 5-15 parts by weight.

4. The method for preparing a high thermal conductivity polytetrafluoroethylene ceramic composite film according to claim 1, characterized in that: The base film is any one of polyimide film, aluminum foil, copper foil or stainless steel foil.

5. The method for preparing a high thermal conductivity polytetrafluoroethylene ceramic composite film according to claim 1, characterized in that: Taking the total volume of the mixed filler as 100 parts, the volume ratio of spherical boron nitride is 10-20 vol%, the volume ratio of flake boron nitride is 15-30 vol%, and the volume ratio of the total amount of spherical silicon dioxide and spherical aluminum oxide is 50-75 vol%.

6. An application of a high thermal conductivity polytetrafluoroethylene ceramic composite membrane, characterized in that: The method is used for preparing a high thermal conductivity polytetrafluoroethylene ceramic-based high-frequency copper-clad laminate, comprising the following steps: cutting a high thermal conductivity polytetrafluoroethylene ceramic composite film prepared by the preparation method according to any one of claims 1 to 5, laminating one or more layers thereof, covering both sides or one side with copper foil, laminating in a vacuum high-temperature press to obtain a high thermal conductivity polytetrafluoroethylene ceramic-based high-frequency copper-clad laminate; the lamination temperature is 350-400°C; the thermal conductivity of the high thermal conductivity high-frequency copper-clad laminate with a thickness of 1.0 mm is not less than 1.2 W / (m•K).

Citation Information

Patent Citations

  • Preparation method of polytetrafluoroethylene (PTFE) composite dielectric substrate

    CN104175686A

  • Microwave circuit boards

    US4335180A

  • PTFE-ceramic slurry for high-frequency microwaves, sintered film of PTFE-ceramic slurry and preparation method and application of PTFE-ceramic slurry and sintered film

    CN115594512A

  • Preparation method for polytetrafluoroethylene composition, polytetrafluoroethylene composition, forming product, conductive pipe, heat conduction film, and substrate ccl

    WO2020114419A1